Discussion on "Sequential detection/isolation of abrupt changes" by Igor V. Nikiforov. Issue 3 (2nd July 2016) - Tartakovsky, Alexander G.
ABSTRACT: Simultaneous sequential changepoint detection and isolation is a challenging theoretical and practical direction of research. Professor Igor Nikiforov's article provides an excellent review of the state-of-the-art literature in this important field. This discussion addresses several issues and extensions important for modern applications of sequential methodology.